Effect of geopolymerization on geotechnical characteristics of palm kernel shell ash stabilized laterite - Adekemi Loretta AYODELE; Raymond AJAYI; Samuel Temiloluwa ADEYEMO (Journal of Materials and Engineering Structures)
Laterite soils (LS) in tropical and subtropical regions exhibit poor engineering properties, making them unsuitable for road construction application. This study examined impact of alkaline activation on palm kernel shell ash (PKSA) stabilized LS. LS properties such as Liquid Limit (LL), Plastic Limit (PL), Optimal Moisture Content, Maximum Dry Density, and California Bearing Ratio (CBR) were determined to ascertain whether it is suitable as a roadway building material. The LS was mixed with different proportions (3, 6, and 9%) of PKSA only and then with an alkaline activator (i.e. 10 M Na2SiO3/NaOH). The earlier mentioned properties of the stabilized LS were determined. An X-ray diffraction test was conducted to examine the mineral composition of PKSA. The results show that the LS, in its natural state, is unsuitable for road construction applications without proper stabilization. Increasing the percentage of PKSA decreased LL, OMC and MDD for PKSA-based and PKSA-geopolymer-based stabilized LS. Furthermore, the CBR of PKSA stabilized soil improved by 77%. Upon further addition of alkaline activator, the CBR value increased by 50% when compared with the natural soil. It was concluded that adding an alkaline activator significantly impacts soil properties for construction. This environmentally friendly method can contribute to sustainable soil stabilization practices in tropical and subtropical regions.